Trends in Hospital Management and Administration Research: A Bibliometric Analysis of International Publications - Dian Pratiwi (P3M Stia Al Gazali Barru and Meraja media, 2026)
[Full Paper] to pdf Copyright (c) 2026 Meraja journal